2019
DOI: 10.1101/632083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pluronic gel-based burrowing assay for rapid assessment of neuromuscular health inC. elegans

Abstract: Whole-organism phenotypic assays are central to the assessment of neuromuscular function and health in model organisms such as the nematode C. elegans. In this study, we report a new assay format for engaging C. elegans in burrowing that enables rapid assessment of nematode neuromuscular health. In contrast to agar environments that pose specific drawbacks for characterization of C. elegans burrowing ability, here we use the optically transparent and biocompatible Pluronic F-127 gel that transitions from liqui… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The C. elegans body wall muscle is the tissue most directly involved in long-term exercise training and thus we sought to characterize additional aspects of body wall muscle performance and health consequent to exercise. We recently developed a burrowing assay, in which nematodes are stimulated to move through a Pluronic F-127 gel (a hydrogel that transitions from liquid to gel at safe temperatures for C. elegans survival) toward a chemoattractant (26). We loaded liquid-phase Pluronic F-127 on top of C. elegans in 12-well plates, and allowed the Pluronic F-127 to quickly gel at room temperature, trapping animals under the gel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans body wall muscle is the tissue most directly involved in long-term exercise training and thus we sought to characterize additional aspects of body wall muscle performance and health consequent to exercise. We recently developed a burrowing assay, in which nematodes are stimulated to move through a Pluronic F-127 gel (a hydrogel that transitions from liquid to gel at safe temperatures for C. elegans survival) toward a chemoattractant (26). We loaded liquid-phase Pluronic F-127 on top of C. elegans in 12-well plates, and allowed the Pluronic F-127 to quickly gel at room temperature, trapping animals under the gel.…”
Section: Resultsmentioning
confidence: 99%
“…2 A ). In this 3D gel environment, animals with a better neuromuscular performance reach the surface faster and in higher numbers (26). After a 3+3+2+2 training regimen, Ad5 exercised nematodes reached the gel surface at a significantly higher proportion during the 3-h burrowing assay window as compared to their nonexercised control counterparts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Burrowing assay. The burrowing assay was performed as described by Lesanpezeshki et al with some modifications (14). Briefly, we placed fifteen age-matched (24 h post L4) naïve or ethanol-exposed animals at the bottom center of a 12 well plate.…”
Section: Methodsmentioning
confidence: 99%
“…To better simulate the natural locomotion, we performed a modified burrow assay (14), in which naïve control and ethanol-exposed animals are allowed to migrate across a solidified Pluronic F-127 gel layer from the bottom of a 12 well plate to an olfactory attractant on the surface. This assay has been shown to effectively detect even a slight deficit in neuromuscular function (14). We found that compared to naïve animals ethanol-exposed animals had difficulties in reaching the surface (Fig.…”
Section: Ethanol Causes Muscle Dysfunction In C Elegansmentioning
confidence: 99%
“…For all samples, we performed a modified gel burrowing assay (Figure 4a) by transferring the nematodes and casting them in Pluronic F127 in a well plate. 33 The surface was coated with E. coli OP-50 lysate as a food source and to attract the nematodes, and the number of C. elegans that penetrated to the surface was counted. Nematode mobility was quantified based on their total track coverage using edge detection (Figures 4b−d, S9, and S10).…”
mentioning
confidence: 99%